Forest Resource Dependency and Livelihood Challenges of the People in Mangrove Ecosystem of the Indian Sundarbans: A Case Study on Gosaba C. D. Block - Mistri, Tapas; Haldar, Notan; Gope, Swarup Majhi (Surviving Sundarbans: Tragedy and Hope, Edition 1, 2025)
This chapter examines the profound reliance of the forest-dependent population in the Gosaba Community Development Block of the Indian Sundarbans on the mangrove ecosystem. The Sundarbans, home to the world’s largest mangrove forest, are crucial for the livelihoods of many residents, particularly those involved in fishing, honey collection, and other forest-related activities. The study, based on data collected from 105 households using purposive snowball sampling, reveals the extent of this dependency and the challenges faced by these communities. Key livelihood practices such as fishing, aquaculture, and honey collection are analysed, highlighting the risks, environmental threats, vulnerability involved and the socio-economic conditions and livelihood support of the population. Through a combination of quantitative and qualitative data, the chapter underscores the need for sustainable management of the mangrove ecosystem to ensure the long-term well-being of the forest-dependent population of Gosaba C.D. block.